Dampak Deregulasi Gula Terhadap Penerimaan Petani Tebu - A. Husni Malian (Forum penelitian Agro Ekonomi, 1998)
EnglishSugar deregulation carried out by the government through INPRES No. 5, 1998 has liberated farmers from compulsory of cane planting. Formerly, the input of sugar raw materials to the factory was assured by the compulsory cane rotation planting by the farmers. Following deregulation, the compulsory planting was abolished. To fulfill the raw material needs, the factory was urged to offer more advantageous sharing system pattern and price level to the farmers. Alternatively that could be done is through sugar agribusiness unit development with vertical coordination where sugar factory as the initiator, motivator and coordinator. By doing so, the role of the government is limited on the effort of preventing a monopsonistic practices that might take place. IndonesianDeregulasi gula yang dilakukan pemerintah melalui Inpres No. 5 tahun 1998 telah membebaskan petani dari kewajiban menanam tebu. Bila sebelum deregulasi pasokan bahan baku pabrik gula dijamin melalui kewajiban penanaman tebu secara bergilir oleh petani, maka setelah adanya deregulasi kewajiban tersebut di hapuskan. Untuk memenuhi kebutuhan bahan bakunya, pabrik gula saat ini dituntut menawarkan pola bagi hasil dan tingkat harga yang lebih menguntungkan petani di bandingkan pengusahaan tanaman pangan. Alternatif yang dapat ditempuh adalah pengembangan Unit Agribisnis Gula (UAG) dengan pola koordinasi vertikal, di mana pabrik gula bertindak sebagai inisiator, motifator dan koordinator. Di sini peran pemerintah dibatasi pada upaya untuk mencegah praktek-praktek monopsonistik yang mungkin terjadi